Identifikasi Jenis Ikan di Sungai Kampar Kiri Desa Mentulik Sebagai Rancangan Buku Saku Biologi SMA Kelas X - Hestathiana; Darmadi; Suwondo (LPPM Institut Pendidikan Nusantara Global, 2026)
This research was conducted in April-May 2025. This research consists of two stages. The first stage is the identification of fish species which includes observations of morphological characteristics and classification. The second stage is the design of a pocket book by integrating the results of the study of fish species identification in the Kampar Kiri River, Mentulik Village. This first stage of research uses a survey method in data collection and uses a purposive sampling technique by observing environmental conditions. The sampling area is divided into three points. The parameters in this study include physical parameters, namely temperature and chemical parameters, namely water pH. The second stage of research is the design of a pocket book using the ADDIE model, but is only carried out at the analysis, design and development stages. The results showed that there were 5 orders and 8 families of 21 types of fish caught in the Kampar Kiri River, Mentulik Village. The dominant orders are the Cypriniformes order with 11 species, the Siluriformes order with 5 species, the Perciformes order with 3 species, the Beloniformes order with 1 species and the Osteoglossiformes order with 1 species. The results of the research on the identification of fish species in the Kampar Kiri River, Mentulik Village can be used as a pocket book for biodiversity material for class X phase E with an average validation score of 3.55 so that the pocket book is included in the very valid category and is suitable for use in the learning process. Keywords: Fish, Kampar Kiri River Mentulik Village, Pocket Book